Brachial flow-mediated vasodilator responses in population-based research: methods, reproducibility and effects of age, gender and baseline diameter. - Herrington, D M; Fan, L; Drum, M; Riley, W A; Pusser, B E; Crouse, J R; Burke, G L; McBurnie, M A; Morgan, T M; Espeland, M A (J Cardiovasc Risk, 2001)
BACKGROUND: Brachial artery ultrasound has been proposed as an inexpensive, accurate way to assess cardiovascular risk in populations. However, analysis and interpretation of these data are not uniform. METHODS: We analysed the relationship between relative and absolute changes in brachial artery diameter in response to flow-mediated dilation and age, gender and baseline diameter among 4,040 ultrasound examinations from subjects aged 14 to 98 years. RESULTS: Reproducibility studies demonstrated intra- and interreader and intrasubject correlations from 0.67 to 0.84 for repeated measures of per cent change in diameter. Per cent change in diameter after flow stimulus was 3.58 +/- 0.10% (mean +/- standard deviation). Corresponding values for baseline diameter and absolute change in diameter were 4.43 +/- 0.87 mm and 0.15 +/- 0.01 mm, respectively. Baseline diameter and its variance were inversely related to per cent change in diameter (P< 0.001). In contrast, absolute change in diameter was more uniform throughout the range of baseline diameters. Baseline diameter was directly related, and per cent change in diameter inversely related, to age (P < 0.001 for all three measures). Time to maximum vasodilator response increased with age (P < 0.001). Women (n=2,315) had significantly larger per cent change in diameter than men (n=1,725) (P < 0.001). However, after adjustment for age and baseline diameter, per cent and absolute change were 5% smaller in women than men (P < 0.05 for both). In multivariate analysis, age was overwhelmingly the most important determinant of absolute change in diameter (P < 0.001). CONCLUSIONS: Automated analysis of brachial flow-mediated vasodilator responses is both feasible and reproducible in large-scale clinical and population-based research.
Keywords: Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Blood Circulation; Brachial Artery; Female; Humans; Male; Middle Aged; Observer Variation; Population Surveillance; Reproducibility of Results; Sex Factors; Vasodilation; Vasodilator Agents

Estrogen replacement and brachial artery flow-mediated vasodilation in older women. - Herrington, D M; Espeland, M A; Crouse, J R; Robertson, J; Riley, W A; McBurnie, M A; Burke, G L (Arterioscler Thromb Vasc Biol, 2001)
It remains unclear whether estrogen therapy (with or without progestin) improves endothelial function in older postmenopausal women with or at risk for coronary heart disease. To address this issue, we analyzed brachial artery flow-mediated vasodilation in the Cardiovascular Health Study, a longitudinal study of cardiovascular risk factors in subjects over 65 years of age. At the tenth annual Cardiovascular Health Study examination, 1662 women returned for follow-up. Eighteen percent (n=291) were current users of estrogen replacement, most of whom (75.9%, n=221) took unopposed estrogen. Brachial artery ultrasound examinations measuring vasodilation in response to a flow stimulus (hyperemia) were performed on 1636 women. There were no statistical differences in brachial flow-mediated vasodilator responses between users and nonusers, even after adjustment for potential confounders. Absence of an effect was most notable in women over 80 years old and in those with established cardiovascular disease. However, among women without clinical or subclinical cardiovascular disease or its risk factors, there was a significant association between hormone replacement therapy use and flow-mediated vasodilator responses (P=0.01). Among older postmenopausal women, favorable vascular effects of estrogen may be limited to those who have not yet developed atherosclerotic vascular disease. These data emphasize the importance of ongoing efforts to determine the role of hormone replacement therapy for primary prevention of cardiovascular disease.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Brachial Artery; Cardiovascular Diseases; Drug Therapy, Combination; Estrogen Replacement Therapy; Estrogens; Female; Humans; Longitudinal Studies; Progestins; Risk Factors; Ultrasonography; Vasodilation

Racial differences in endothelial function in postmenopausal women. - Loehr, Laura R; Espeland, Mark A; Sutton-Tyrrell, Kim; Burke, Gregory L; Crouse, John R; Herrington, David M (Am Heart J, 2004)
OBJECTIVE: Racial differences in cardiovascular mortality among women remain largely unexplained. Preliminary data suggest that African American and Caucasian differences in endothelial function may parallel differential cardiovascular disease (CVD) risk in women. To further study differences in endothelial function between African American and Caucasian women, we analyzed measures of brachial artery flow-mediated dilation (FMD) in women enrolled in the Cardiovascular Health Study (CHS). METHODS AND RESULTS: Brachial artery FMD was measured in the fasting state using established ultrasound techniques in 1330 Caucasian and 297 African American female participants in CHS (mean age 78.4 +/- 4.4 years). General linear models were used to compare FMD between African American and Caucasian women after adjusting for baseline brachial diameter, hypertension, diabetes, smoking, cholesterol, systolic blood pressure, body mass index, waist/hip ratio, age, education, income level; use of angiotensin-converting enzyme inhibitors, beta-blockers, nitroglycerin, estrogens and lipid-lowering drugs; and presence of clinical or subclinical disease. Adjusted absolute change and percent change in brachial artery diameter was significantly reduced in African American women compared with Caucasian women (P <.0001 and P =.0002, respectively). Similar results were found when the women were stratified by history of CVD (- CVD, P =.02; + CVD, P =.001) and CVD or subclinical vascular disease (- disease, P =.01, + disease, P =.03). CONCLUSIONS: In this cohort, brachial artery FMD was lower in African American women compared to Caucasian women, and this difference persisted after adjustment by multivariable analysis. The increased CVD risk in African American women may be related to impaired endothelial function. It remains to be determined whether African American women may uniquely benefit by interventions designed to improve endothelial health.
Keywords: African Continental Ancestry Group; Aged; Brachial Artery; Cohort Studies; Endothelium, Vascular; European Continental Ancestry Group; Female; Humans; Multivariate Analysis; Postmenopause; Risk Factors; Vasodilation

Brachial flow-mediated dilation predicts incident cardiovascular events in older adults: the Cardiovascular Health Study. - Yeboah, Joseph; Crouse, John R; Hsu, Fang-Chi; Burke, Gregory L; Herrington, David M (Circulation, 2007)
BACKGROUND: The relationship between impaired brachial flow-mediated dilation (FMD) and subsequent clinical cardiovascular events is not well established, especially in older adults whose FMD is often diminished. We assessed the hypothesis that FMD predicts incident cardiovascular events in a population-based cohort of older adults. METHODS AND RESULTS: FMD was measured at the 1997 to 1998 Cardiovascular Health Study clinic visit in 2792 adults aged 72 to 98 years (82.7% white, 58.6% women) recruited at 4 clinic sites in the United States. Log-rank test and Cox proportional hazard models were used to examine the association between FMD and adjudicated cardiovascular events. A total of 674 subjects (24.1%) had an adjudicated event over the 5-year follow-up period. Event-free survival rates for cardiovascular events were significantly higher in subjects with FMD greater than the sex-specific medians than in subjects with FMD less than or equal to the sex-specific medians (78.3% versus 73.6%, log-rank P=0.006). FMD remained a significant predictor of cardiovascular events after adjustment for age, gender, diabetes mellitus, cigarette smoking, systolic and diastolic blood pressure, baseline cardiovascular disease status, and total cholesterol (hazard ratio, 0.91 [95% CI, 0.83 to 0.99], P=0.02 per unit SD of FMD) but added only approximately 1% to the prognostic accuracy of the best Cox model. Brachial artery diameter was also predictive of CV events in the adjusted Cox proportional hazard model (hazard ratio, 1.12 [95% CI, 1.02 to 1.28], P=0.025) and also added approximately 1% to the accuracy of our best Cox model. CONCLUSIONS: FMD is a predictor of future cardiovascular events but adds very little to the prognostic accuracy of traditional cardiovascular risk scores/factors in older adults. FMD and brachial artery diameter may have similar predictive values for cardiovascular events in older adults.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Biomarkers; Brachial Artery; Cardiovascular Diseases; Cohort Studies; Disease-Free Survival; Endothelium, Vascular; Female; Hemorheology; Humans; Hyperemia; Male; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Prospective Studies; Reproducibility of Results; Risk Factors; Stress, Mechanical; Tourniquets; Ultrasonography; United States; Vasodilation

Association between brachial artery reactivity and cardiovascular disease status in an elderly cohort: the cardiovascular health study. - Yeboah, Joseph; Sutton-Tyrrell, Kim; McBurnie, Mary Ann; Burke, Gregory L; Herrington, David M; Crouse, John R (Atherosclerosis, 2008)
BACKGROUND AND OBJECTIVES: The association of brachial flow-mediated dilation (FMD) and cardiovascular disease (CVD) status is unclear especially in older adults whose FMD is greatly diminished. We assessed the association of FMD and the presence or absence of subclinical and clinical CVD in a population based cohort of older adults. METHODS AND RESULTS: FMD was measured in 2971 adults aged 72-98 years (mean age 78.6 years) who participated in the Cardiovascular Health Study. Multiple linear regression analysis was used to examine the association between FMD and CVD status (clinical, subclinical and free of CVD). Out of 2791 with complete data, 82.7% were Caucasians and 59% females. Seven hundred and forty-three were classified as having clinical CVD, 607 as subclinical CVD and 1441 as neither clinical CVD nor subclinical CVD (CVD free). FMD was higher in the CVD free group compared with either the clinical (3.13+/-0.05% vs 2.93+/-0.07%, p=0.025) or the subclinical CVD group (3.13+/-0.05% vs 2.95+/-0.08%, p=0.05) after adjusting for covariates. There was no significant difference between the FMD of subjects with clinical and subclinical CVD (2.93+/-0.07% vs 2.95+/-0.08%, p=0.84). Similar but inverted associations were observed between height adjusted brachial artery diameter (BAD) and CVD status. However, FMD and BAD had poor diagnostic accuracies for identifying older adults with subclinical CVD. CONCLUSION: Among older adults, those with either clinical or subclinical CVD have lower FMD than CVD free subjects. BAD showed similar but inverted associations with CVD status in this cohort. FMD and BAD had poor diagnostic accuracies for identifying older adults with subclinical CVD.
Keywords: Aged; Aged, 80 and over; Biomarkers; Brachial Artery; Cardiovascular Diseases; Cohort Studies; Female; Hemorheology; Humans; Male; Peripheral Vascular Diseases; ROC Curve; Ultrasonography; Vasodilation

Relationship between brachial flow-mediated dilation and carotid intima-media thickness in an elderly cohort: the Cardiovascular Health Study. - Yeboah, Joseph; Burke, Gregory L; Crouse, John R; Herrington, David M (Atherosclerosis, 2008)
OBJECTIVE: The aim of this study was to determine the relationship between brachial flow-mediated dilation (FMD) and carotid intima-media thickness (IMT) in a large multi-ethnic elderly cohort. BACKGROUND: Brachial flow-mediated dilation (FMD) is a physiologic measure and carotid IMT is an anatomic structural measure of subclinical atherosclerosis. Both brachial FMD and carotid IMT have been associated with cardiovascular risk factors and cardiovascular events. The relationship between brachial FMD and carotid IMT is less clear especially in older adults. METHODS: Brachial FMD, carotid IMT and traditional cardiovascular risk factors were measured in 2338 adults, age 72-98 years who were participants in the Cardiovascular Health Study. The relationship between FMD and IMT was assessed both unadjusted and also after adjusting for age, gender and race/ethnicity, BMI, HDL, LDL, systolic and diastolic blood pressure, serum creatinine, current smoking, diabetes mellitus, hormone therapy and prior CVD. RESULTS: Both brachial FMD and carotid IMT correlated significantly with age, HDL levels, waist/hip ratio, serum cholesterol and number of CV risk factors. Brachial FMD was not associated with CCA IMT in this elderly cohort (Pearson partial correlation coefficient=-0.0252, p=0.222). In the adjusted linear regression model with CCA IMT as the dependent variable, brachial FMD was also not associated with CCA IMT (beta coefficient=-0.006, p=0.470). CONCLUSION: Brachial FMD and CCA IMT are not related in population-based older adults. Brachial FMD and CCA IMT may be distinct and independent stages in the complex atherosclerotic process.
Keywords: Age Factors; Aged; Aged, 80 and over; Brachial Artery; Carotid Arteries; Carotid Artery Diseases; Cohort Studies; Female; Hemorheology; Humans; Male; Tunica Intima; Tunica Media; Ultrasonography; Vasodilation

Brachial artery diameter, blood flow and flow-mediated dilation in sleep-disordered breathing. - Chami, Hassan A; Keyes, Michelle J; Vita, Joseph A; Mitchell, Gary F; Larson, Martin G; Fan, Shuxia; Vasan, Ramachandran S; O'Connor, George T; Benjamin, Emelia J; Gottlieb, Daniel J (Vasc Med, 2009)
Clinic-based, case-control studies linked sleep-disordered breathing (SDB) to markers of endothelial dysfunction. We attempted to validate this association in a large community-based sample, and evaluate the relation of SDB to arterial diameter and peripheral blood flow. This community-based, cross-sectional observational study included 327 men and 355 women, aged 42-83 years, from the Framingham Heart Study site of the Sleep Heart Health Study. The polysomnographically derived apnea-hypopnea index and the hypoxemia index (percent sleep time with oxyhemoglobin saturation below 90%) were used to quantify the severity of SDB. Brachial artery ultrasound measurements included baseline diameter, percent flow-mediated dilation, and baseline and hyperemic flow velocity and volume. The baseline brachial artery diameter was significantly associated with both the apnea-hypopnea index and the hypoxemia index. The association was diminished by adjustment for body mass index, but remained significant for the apnea-hypopnea index. Age-, sex-, race- and body mass index-adjusted mean diameters were 4.32, 4.33, 4.33, 4.56, 4.53 mm for those with apnea-hypopnea index < 1.5, 1.5-4.9, 5-14.9, 15-29.9, >/= 30, respectively; p = 0.03. Baseline flow measures were associated with the apnea-hypopnea index but this association was non-significant after adjusting for body mass index. No significant association was observed between measures of SDB and percent flow-mediated dilation or hyperemic flow in any model. In conclusion, this study supports a moderate association of SDB and larger baseline brachial artery diameter, which may reflect SDB-induced vascular remodeling. This study does not support a link between SDB and endothelial dysfunction as measured by brachial artery flow-mediated dilation.
Keywords: Adult; Aged; Aged, 80 and over; Blood Flow Velocity; Brachial Artery; Cross-Sectional Studies; Female; Humans; Hyperemia; Hypoxia; Laser-Doppler Flowmetry; Male; Middle Aged; Polysomnography; Regional Blood Flow; Severity of Illness Index; Sleep Apnea Syndromes; Ultrasonography; Vasodilation

Fibrosis-related biomarkers and large and small vessel disease: the Cardiovascular Health Study. - Agarwal, Isha; Arnold, Alice; Glazer, Nicole L; Barasch, Eddy; Djoussé, Luc; Fitzpatrick, Annette L; Gottdiener, John S; Ix, Joachim H; Jensen, Richard A; Kizer, Jorge R; Rimm, Eric B; Siscovick, David S; et al. (Atherosclerosis, 2015)
OBJECTIVE: Fibrosis has been implicated in a number of pathological, organ-based conditions of the liver, kidney, heart, and lungs. The objective of this study was to determine whether biomarkers of fibrosis are associated with vascular disease in the large and/or small vessels. METHODS: We evaluated the associations of two circulating biomarkers of fibrosis, transforming growth factor-β (TGF-β) and procollagen type III N-terminal propeptide (PIIINP), with incident peripheral artery disease (PAD) and subclinical macrovascular (carotid intima-media thickness, flow-mediated vasodilation, ankle-brachial index, retinal vein diameter), and microvascular (retinal artery diameter and retinopathy) disease among older adults in the Cardiovascular Health Study. We measured TGF-β and PIIINP from samples collected in 1996 and ascertained clinical PAD through 2011. Measurements of large and small vessels were collected between 1996 and 1998. RESULTS: After adjustment for sociodemographic, clinical, and biochemical risk factors, TGF-β was associated with incident PAD (hazard ratio [HR] = 1.36 per doubling of TGF-β, 95% confidence interval [CI] = 1.04, 1.78) and retinal venular diameter (1.63 μm per doubling of TGF-β, CI = 0.23, 3.02). PIIINP was not associated with incident PAD, but was associated with carotid intima-media thickness (0.102 mm per doubling of PIIINP, CI = 0.029, 0.174) and impaired brachial artery reactivity (-0.20% change per doubling of PIIINP, CI = -0.39, -0.02). Neither TGF-β nor PIIINP were associated with retinal arteriolar diameter or retinopathy. CONCLUSIONS: Serum concentrations of fibrosis-related biomarkers were associated with several measures of large vessel disease, including incident PAD, but not with small vessel disease. Fibrosis may contribute to large vessel atherosclerosis in older adults.
Keywords: Aged; Ankle Brachial Index; Biomarkers; Brachial Artery; Carotid Artery Diseases; Carotid Intima-Media Thickness; Cross-Sectional Studies; Female; Fibrosis; Humans; Incidence; Male; Peptide Fragments; Peripheral Arterial Disease; Predictive Value of Tests; Procollagen; Prognosis; Prospective Studies; Retinal Diseases; Risk Factors; Transforming Growth Factor beta; United States; Vasodilation